2018
DOI: 10.1007/s00264-018-4007-7
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic effects of percutaneous kyphoplasty on osteoporotic vertebral compression fractures with or without intravertebral cleft

Abstract: Our results suggested that unilateral PKP was a safe and reliable treatment for OVCFs with IVC. However, the IVC group had higher incidence of bone cement leakage during surgery and more severe KA rebound during the follow-up period. Therefore, to reduce the incidence of bone cement leakage, it is very important to evaluate the pre-operative imaging and inject the cement carefully and repetitiously. When cement leakages are found, injection should be stopped immediately. Longer rehabilitation interventions suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 18 publications
3
31
2
Order By: Relevance
“…This study found that the leakage rate of bone cement in the K and O groups were 14.29% and 8.57%, respectively, which may be related to accurate preoperative surgical approach measurement, careful intraoperative operation and not pursue the maximum amount of bone cement. There was no significant difference in cement leakage rate between the two groups, which was consistent with previous research results [42,43]. Among the 219 patients with single thoracolumbar OVCFs, 29 cases(13.22%) occurred non-surgical vertebral fractures [44].…”
Section: Resultssupporting
confidence: 90%
“…This study found that the leakage rate of bone cement in the K and O groups were 14.29% and 8.57%, respectively, which may be related to accurate preoperative surgical approach measurement, careful intraoperative operation and not pursue the maximum amount of bone cement. There was no significant difference in cement leakage rate between the two groups, which was consistent with previous research results [42,43]. Among the 219 patients with single thoracolumbar OVCFs, 29 cases(13.22%) occurred non-surgical vertebral fractures [44].…”
Section: Resultssupporting
confidence: 90%
“…Patients often suffer intractable lumbar and back pain, and even nerve injury. Imaging examination shows IVC or localized uid lling in the vertebral body [14]. In this study, the course of Kümmell's disease was signi cantly longer than the course of OVCFs.…”
Section: Resultsmentioning
confidence: 50%
“…In this study, VAS and ODI postoperatively were significantly reduced in both groups and were maintained to the last follow-up. Li et al [27] found that VAS and ODI were significantly improved at the last follow-up compared with those before treatment in patients with KD after intensive vertebral treatment. In this study, spongy group is superior to the blocky group in terms of pain relief and functional recovery.…”
Section: Resultsmentioning
confidence: 98%
“…A small dose of bone cement can restore the mechanical properties of the fractured vertebral body, and the amount of bone cement injected has no obvious correlation with the analgesic effect [26,27].…”
Section: Resultsmentioning
confidence: 99%